Microwave synthesis of barium iron niobate and dielectric properties - Nipaphat Charoenthai (2018)
A microwave synthesis was applied to prepare barium iron niobate (BFN) powders for the first time. Pure perovskite phase of BFN with a cubic symmetry was obtained when precursors were calcined at 850 °C for 14 h. Average particle size of pure BFN powder was estimated to be in submicron range. The examination of dielectric spectra indicated that BFN ceramics prepared by the present method exhibited rather high dielectric constant (∼ 30,000 at 300 °C for 1 kHz) with low dielectric loss (less than 0.6). © 2008 Elsevier B.V. All rights reserved.